Desymmetrization of cyclic 1,3-Diketones under N-Heterocyclic carbene organocatalysis: access to organofluorines with multiple stereogenic centers - Wang, Guanjie (2022)
Symmetric 1,3-diketones with fluorine or fluorinated substituents on the prochiral carbon remain to be established. Herein, we have developed a novel prochiral fluorinated oxindanyl 1,3-diketone and successfully applied these substrates in carbene-catalyzed asymmetric desymmetrization. Accordingly, a versatile strategy for asymmetric generation of organofluorines with fluorine or fluorinated methyl groups has been developed. Multiple stereogenic centers were selectively constructed with satisfactory outcomes. Structurally diverse enantioenriched organofluorines were generated with excellent results in terms of yields, diastereoselectivities, and enantioselectivities. Notably, exchanging fluorinated methyl groups to fluorine for this prochiral 1,3-diketones leads to switchable stereoselectivity. Mechanistic aspects and origin of stereoselectivity were studied by DFT calculations. Notably, some of the prepared organofluorines demonstrated competitive antibacterial activities.